In-Depth Assessment of Individuals with Bipolar Affective Disorder - Mohammad Fauzan Aqil Muhariyono; Qurrota A'yuni Fitriana (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2024)
Bipolar Affective Disorder is a type of severe mental illness characterized by extreme mood fluctuations, ranging from deep depressive phases to highly manic episodes. This study aims to gain a deeper understanding of the characteristics of Bipolar Affective Disorder through a case study of a patient treated at a psychiatric clinic in Surabaya. The research employs observational methods, interviews, and a literature review to collect relevant data with a case study approach. The assessment results indicate that the patient experiences significant mood changes, from profound sadness to extreme euphoria, influenced by traumatic childhood experiences. Through analysis using Erikson's Psychosocial Development Theory, the study finds that unresolved psychosocial conflicts from the past can exacerbate the patient's condition. These findings highlight the importance of in-depth assessments to understand the severity and type of disorder in patients with Bipolar Affective Disorder, as well as the appropriate interventions needed to improve their quality of life.